EXPLORING ECOPEDAGOGY THROUGH LOCAL WISDOM-BASED SOCIAL STUDIES LEARNING FOR JUNIOR HIGH SCHOOL STUDENTS IN KUDUS - Sulaswari, Misroh; Fatah, Ahmad; Fatmawati, Noor; Falaq, Yusuf (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Ecopedagogy is an approach in education that emphasizes environmental awareness. True education must promote sustainable development through inculcating the character of students who care about the natural and social environment. This study aims to explore the existence of ecopedagogy in education through social studies learning based on local wisdom which has been taking place for junior high school students in Kudus. The method used in this study is descriptive qualitative through interviews with a number of social studies teachers and students at junior high schools in Kudus who were randomly selected. The results of the study found that social studies learning at junior high schools in Kudus taught several local wisdoms such as wiwit kopi, rebo wekasan, jenang tebokan, and sego jangkrik which are loaded with the meaning of environmental awareness according to the concept of ecopedagogy. Local traditions and culture in Kudus are not just ritualization, but the meaning contained in these traditions teaches students to respect the universe so that balance will continue. The concept of ecopedagogy in education needs to be raised, one of which is social studies learning based on local wisdom. So that sustainable development will continue to be inherited properly.